Role of Vascular Smooth Muscle Cell Plasticity and Interactions in Vessel Wall Inflammation - Sorokin, Vitaly; Vickneson, Keeran; Kofidis, Theo; Woo, Chin Cheng; Lin, Xiao Yun; Foo, Roger; Shanahan, Catherine M. (Frontiers in Immunology, 2020)
The pathobiology of atherosclerotic disease requires further elucidation to discover new approaches to address its high morbidity and mortality. To date, over 17 million cardiovascular-related deaths have been reported annually, despite a multitude of surgical and nonsurgical interventions and advances in medical therapy. Existing strategies to prevent disease progression mainly focus on management of risk factors, such as hypercholesterolemia. Even with optimum current medical therapy, recurrent cardiovascular events are not uncommon in patients with atherosclerosis, and their incidence can reach 10-15% per year. Although treatments targeting inflammation are under investigation and continue to evolve, clinical breakthroughs are possible only if we deepen our understanding of vessel wall pathobiology. Vascular smooth muscle cells (VSMCs) are one of the most abundant cells in vessel walls and have emerged as key players in disease progression. New technologies, including in situ hybridization proximity ligation assays, in vivo cell fate tracing with the CreERT2-loxP system and single-cell sequencing technology with spatial resolution, broaden our understanding of the complex biology of these intriguing cells. Our knowledge of contractile and synthetic VSMC phenotype switching has expanded to include macrophage-like and even osteoblast-like VSMC phenotypes. An increasing body of data suggests that VSMCs have remarkable plasticity and play a key role in cell-to-cell crosstalk with endothelial cells and immune cells during the complex process of inflammation. These are cells that sense, interact with and influence the behavior of other cellular components of the vessel wall. It is now more obvious that VSMC plasticity and the ability to perform nonprofessional phagocytic functions are key phenomena maintaining the inflammatory state and senescent condition and actively interacting with different immune competent cells.